Profil mikroskopis sedimen urin pada kondisi glukosuria di Laboratorium Klinik Prodia, Banda Aceh - Siti Hadijah; Rahmayanti Rahmayanti; Erlinawati Erlinawati (Politeknik Kesehatan Kemenkes Aceh, 2022)
Background: Laboratory examination of urine (urinalysis) is crucial in establishing various diagnoses. Urine examination can be done through macroscopic examination, including color, clarity, and microscopic examination of urine sediment (U-sed) and urine chemical examination such as glucose. Urine sediment is insoluble elements such as erythrocytes, leukocytes, epithelial cells, thorax, bacteria, crystals, fungi, and parasites originating from the blood, kidneys, and urinary tract. Glucosuria is a condition where glucose is found in the urine, and when excessive >180 mg/dL can experience hyperglycemia, the impact is to damage the capillary blood vessels in the kidneys. U-sed is used to identify sediment elements that can be used to detect kidney and urinary tract abnormalities.Objectives: This study aims to determine the U-sed profile in glucosuria at Prodia Clinical Laboratory, Banda Aceh.Methods: Descriptive research using an experimental design and analyzing secondary data from patients with glucosuria and referred for U-sed examination at Prodia Clinical Laboratory, Banda Aceh Branch. The study was conducted in Mai 2022, with a total sample size of 24 respondents. Microscopic examination U-sed data was processed in stages starting from editing, coding, entry, and cleaning data. Data were only analyzed descriptively using frequency distribution.Results: The results of the study of the U-sed profile in patients with glucosuria conditions were abnormal flat epithelial cells (50,0%), the occurrence of leukocyturia (67,7%), the occurrence of hematuria (70,8%), and other sediments that were above normal only 25,0% of patients. Thus, the U-sed profile in patients with glucosuria conditions may be pathological such as infection, inflammation, and stones in the urinary tract.Conclusion: Some of the MSU profile data in patients who performed laboratory examinations at Prodia Banda Aceh showed above-normal threshold values, such as the data of flat epithelial cells, leukocytes, erythrocytes, and some other sentiments that were above normal had a low frequency. Patients who perform urine tests are at risk of infection and inflammation of the urinary tract and even the risk of kidney stones.